Corrosion study of TiN, TiAlN and CrN multilayer coatings deposit on martensitic stainless steel by arc cathodic physical vapour deposition. (30th January 2019) - Olia, Hossein; Ebrahimi-Kahrizsangi, Reza; Ashrafizadeh, Fakhreddin; Ebrahimzadeh, Iman
Abstract: In this study, several multilayers nitride coatings were deposited on 17-4 PH stainless steel by employing a cathodic arc physical vapour deposition process to improve the resistance of this stainless steel in corrosive solution environment. Morphology and structure of the coatings were investigated by scanning electron microscopy and x-ray diffraction. Nano instrument equipped method was used to obtain the hardness of the coatings. To evaluate the corrosion resistance, the potentiodynamic polarization and electrochemical impedance spectroscopy tests, in 3.5% NaCl solution, were carried out. The potentiodynamic tests revealed the E corr shifted to more positive potential in all nitride coated that deposited on the substrate. Specimens with CrN/CrAlN multilayer coating revealed superior corrosion resistance compared with substrate and TiN/TiAlN multilayer coating. The electrochemical impedance spectroscopy measurements represent a single time constant lead to corrosion of the coatings without degradation of the substrate. The results also showed that aluminum content of the coating improved the protective role of the layer because of its ability to form the passive film.